One-way allosteric communication between the two disulfide bonds in tissue factor - Zhou, Beifei; Hogg, Philip J.; Gräter, Frauke (Biophysical journal, 2017)
Tissue factor (TF) is a transmembrane glycoprotein that plays distinct roles in the initiation of extrinsic coagulation cascade and thrombosis. TF contains two disulfide bonds, one each in the N-terminal and C-terminal extracellular domains. The C-domain disulfide, Cys186-Cys209, has a −RHStaple configuration in crystal structures, suggesting that this disulfide carries high pre-stress. The redox state of this disulfide has been proposed to regulate TF encryption/decryption. Ablating the N-domain Cys49-Cys57 disulfide bond was found to increase the redox potential of the Cys186-Cys209 bond, implying an allosteric communication between the domains. Using molecular dynamics simulations, we observed that the Cys186-Cys209 disulfide bond retained the −RHStaple configuration, whereas the Cys49-Cys57 disulfide bond fluctuated widely. The Cys186-Cys209 bond featured the typical −RHStaple disulfide properties, such as a longer S-S bond length, larger C-S-S angles, and higher bonded prestress, in comparison to the Cys49-Cys57 bond. Force distribution analysis was used to sense the subtle structural changes upon ablating the disulfide bonds, and allowed us to identify a one-way allosteric communication mechanism from the N-terminal to the C-terminal domain. We propose a force propagation pathway using a shortest-pathway algorithm, which we suggest is a useful method for searching allosteric signal transduction pathways in proteins. As a possible explanation for the pathway being one-way, we identified a pronounced lower degree of conformational fluctuation, or effectively higher stiffness, in the N-terminal domain. Thus, the changes of the rigid domain (N-terminal domain) can induce mechanical force propagation to the soft domain (C-terminal domain), but not vice versa.
Gesehen am 06.08.2018